Association of circulating vitamin levels with thyroid diseases: a Mendelian randomization study - Zhang, Wenke; Liu, Erhao; Que, Huafa (Frontiers in Endocrinology, 2024)
Background: Previous observational studies have shown conflicting results of vitamins supplementation for thyroid diseases. The causal relationships between vitamins and thyroid diseases are unclear. Therefore, we conducted a two-sample bidirectional Mendelian randomization (MR) study to explore association of circulating vitamin levels with thyroid diseases. Methods: We performed a bidirectional MR analysis using genome-wide association study (GWAS) data. Genetic tool variables for circulating vitamin levels include vitamins A, B9, B12, C, D, and E, Genetic tool variables of thyroid diseases include autoimmune hyperthyroidism, autoimmune hypothyroidism, thyroid nodules(TNs), and Thyroid cancer(TC). Inverse-variance weighted multiplicative random effects (IVW-RE) was mainly used for MR Analysis, weighted median(WM) and MR Egger were used as supplementary methods to evaluate the relationships between circulating vitamin levels and thyroid diseases. Sensitivity and pluripotency were evaluated by Cochran's Q test, MR-PRESSO, Radial MR, MR-Egger regression and leave-one-out analysis.Results: Positive MR evidence suggested that circulating vitamin C level is a protective factor in autoimmune hypothyroidism(ORIVW-RE=0.69, 95%CI: 0.58-0.83, p = 1.05E-04). Reverse MR Evidence showed that genetic susceptibility to autoimmune hyperthyroidism is associated with reduced level of circulating vitamin A(ORIVW-RE = 0.97, 95% CI: 0.95 -1.00, p = 4.38E-02), genetic susceptibility of TNs was associated with an increased level of circulating vitamin D(ORIVW-RE = 1.02, 95% CI:1.00 -1.03, p = 6.86E-03). No causal and reverse causal relationship was detected between other circulating vitamin levels and thyroid diseases.Our findings provide genetic evidence supporting a bi-directional causal relationship between circulating vitamin levels and thyroid diseases. These findings provide information for the clinical application of vitamins prevention and treatment of thyroid diseases.